An arabinogalactan from Lycium barbarum attenuates DSS-induced chronic colitis in C57BL/6J mice associated with the modulation of intestinal barrier function and gut microbiota. Issue 20 (27th August 2021) - Cao, Cui; Zhu, Beiwei; Liu, Zhengqi; Wang, Xue; Ai, Chunqing; Gong, Guiping; Hu, Minghua; Huang, Linjuan; Song, Shuang
Abstract : LBP-3 is a homogeneous arabinogalactan with an identified structure and a molecular weight of 99.9 ± 4.2 kDa from Lycium barbarum . LBP-3 alleviates DSS-induced chronic colitis by improving the gut barrier and restoring the gut microbiota and its metabolites. Abstract : Ulcerative colitis (UC) is an incurable chronic inflammation of the enteric tract. The aim of this study was to investigate the protective effects of arabinogalactan from Lycium barbarum on DSS-induced chronic colitis. A homogeneous arabinogalactan was isolated and purified from L. barbarum, named LBP-3, which mainly consisted of arabinose and galactose with a molar ratio of 1.00 : 0.82. LBP-3 treatment remarkably alleviated body weight loss, histopathological damage and the overproduction of pro-inflammatory cytokines and enzymes in UC mice. Additionally, the intestinal barrier integrity was partially recovered by the up-regulated expression of MUC2 and tight junction proteins. Moreover, the gut microbiota shift was reversed by LBP-3 administration by enriching potential probiotic bacteria ( e.g., Ruminococcaceae) and inhibiting the proliferation of harmful bacteria ( e.g., Enterobacteriaceae). Furthermore, SCFAs, as major metabolites of LBP-3 fermentation by gut microbiota, were also promoted so as to maintain relatively favorable intestinal homeostasis. Overall, our findings suggested LBP-3 from L. barbarum could be a potential therapeutic candidate against UC via improving intestinal barrier function and partially restoring gut microbiota and its metabolites.